A "sacless hernia" with the orifice obscured by a preperitoneal lipoma: A case report. (January 2022) - Nishida, Kazuhiro; Ochiai, Shingo; Lefor, Alan Kawarai
Abstract: Introduction and importance: With the widespread use of laparoscopic inguinal hernia repair, it is known that some clinically evident inguinal hernias lack a peritoneal sac and are referred to as "sacless hernias". Presentation of case: A 61-year-old man presented with a left inguinal bulge. On physical examination, the diagnosis of bilateral inguinal hernias was made, and laparoscopic transabdominal repair was performed. Intraoperatively, the left peritoneal hernia orifice was not identified from the peritoneal cavity and there was only a lipoma. Pressing the lipoma with forceps from inside the peritoneum confirmed the presence of a hernia. The preperitoneal space was opened and the hernia orifice revealed. Discussion: The terminology and definition of sacless hernias are poorly defined, even though this is not a rare condition. Consistent with Russell's dogma, there are arguments that any prolapse can only be called a hernia if there is an accompanying peritoneal sac. The proportion of patients with sacless hernias and pure cord lipomas are very similar and these conditions are often confused. Detailed and repeated physical examination may distinguish a sacless hernia from a pure lipoma. A watchful waiting strategy is useful and ensures safety. Conclusion: Once the diagnosis of inguinal hernia is made on physical examination, open the preperitoneal cavity if a peritoneal hernia orifice was not identified during laparoscopy. Highlights: The exact terminology and definition of a "sacless hernia" is still unclear and there were very few literatures, despite this situation has been commonly known. Attention should be paid not to confuse a sacless hernia with a spermatic cord lipoma. Preoperative physical examination and diagnosis is a key to distinguish them. Once a robust diagnosis of inguinal hernia is made by physical examination, open the preperitoneal cavity if the peritoneal hernia orifice was not identified during laparoscopy.